Aerodynamic analysis of backward swept in HAWT rotor blades using CFD - Salari, Mohammad Sadegh; Boushehri, Behzad Zarif; Boroushaki, Mehrdad (International Journal of Renewable Energy Development, 2018)
The aerodynamical design of backward swept for a horizontal axis wind turbine blade has been carried out to produce more power at higher wind velocities. The backward sweep is added by tilting the blade toward the air flow direction. Computational Fluid Dynamics (CFD) calculations were used for solving the conservation equations in one outer stationary reference frame and one inner rotating reference frame, where the blades and grids were fixed in reference to the rotating frame. The blade structure was validated using Reynolds Averaged Navier-Stokes (RANS) solver in a test case by the National Renewable Energy Laboratory (NREL) VI blades results. Simulation results show considerable agreement with the NREL measurements. Standard K-Îµ turbulence model was chosen for simulations and for the backward swept design process. A sample backward sweep design was applied to the blades of a Horizontal Axis Wind Turbine (HAWT) rotor, and it is obtained that although at the lower wind velocities the output power and the axial thrust of the rotor decrease, at the higher wind velocities the output power increases while the axial thrust decreases. The swept blades have shown about 30 percent increase in output power and about 12 percent decrease in thrust at the wind speed of 14 m/s.Article History: Received June 23rd 2018; Received in revised form Sept 16th 2018; Accepted October 1st 2018; Available onlineHow to Cite This Article: Salari, M.S., Boushehri, B.Z. and Boroushaki, M. (2018). Aerodynamic Analysis of Backward Swept in HAWT Rotor Blades Using CFD. International Journal of Renewable Energy Development, 7(3), 241-249.http://dx.doi.org/10.14710/ijred.7.3.241-249